Adakah Ruang Ijtihad Untuk Isu Homoseks? - Maftuhin, Arif (Musawa Jurnal Studi Gender dan Islam, 2003)
Thus far the views of experts of Islamic jurisprudence regarding homosexuality have been very clear in forbidding it. The Alqur'an, Hadith and Ijma' are the bases of the prohibition on marriages of this kind, although jurists differ in their views on the punishment for homosexual behaviour. Malik, ash-Shafi'i and Ahmad equate the punishment for homosexual acts with that for adultery, whereas Abu Hanifah views it as a ta'zir punishment (one determined by the government). Meanwhile, theÂ· view of some that homosexuality is a natural and predetermined phenomenon presents its own challenges: how will Islamic law respond to the claim that homosexuality is a part of our basic human rights that must be protected?